فاعلية برنامج مقترح قائم على معايير العلوم للجيل القادم "NGSS" لتنمية مهارات الحل الإبداعي للمشكلات لدى تلاميذ الصف الخامس الابتدائي بدولة الكويت - الحربي، غالية; الموجي، أماني محمد سعد الدين; أحمد، أميمة محمد عفيفي (جامعة القاهرة - كلية الدراسات العليا للتربية - الجمعية العربية للدراسات المتقدمة في المناهج العلمية, 2023)
هدف البحث إلى تنمية مهارات الحل الإبداعي للمشكلات لدى تلميذات الصف الخامس الابتدائي باستخدام برنامج مقترح قائم على معايير العلوم للجيل القادم NGSS؛ ولتحقيق هدف البحث أعدت الباحثة مقياس مهارات الحل الإبداعي للمشكلات، والبرنامج المقترح القائم على معايير العلوم للجيل القادم NGSS، متضمنا دليل المعلم وكراس نشاط التلميذ. تم تطبيق أداة البحث ومواده التعليمية على مجموعتين بحثيتين، مكونة من (33) تلميذة في المجموعة التجريبية، و (33) تلميذة في المجموعة الضابطة من تلميذات مدرسة أم جميل العامرية الابتدائية بنات التابعة للإدارة العامة لمنطقة الجهراء التعليمية وذلك في الفصل الدراسي الأول للعام الدراسي 2022/ 2023 م. وأظهرت نتائج البحث وجود فروق ذات دلالة إحصائية بين متوسطي درجات المجموعتين التجريبية والضابطة، في التطبيق البعدي لمقياس مهارات الحل الإبداعي للمشكلات لصالح المجموعة التجريبية، ووجود فروق ذات دلالة إحصائية بين متوسطي درجات المجموعة التجريبية في التطبيقين القبلي والبعدي لمقياس مهارات الحل الإبداعي للمشكلات ككل لصالح التطبيق البعدي، كما أظهرت نتائج البحث فاعلية البرنامج المقترح القائم على معايير العلوم للجيل القادم NGSS في تنمية مهارات الحل الإبداعي للمشكلات لتلميذات الصف الخامس الابتدائي، كما أوصت الباحثة بضرورة الاهتمام بتنمية مهارات الحل الإبداعي للمشكلات لدى تلميذات المرحلة الابتدائية، مع تقديم بعض المقترحات لبحوث مستقبلية. The research aimed to develop the skills of creative problem-solving among fifth-grade female students, using a proposed program based on the Next Generation Science Standards (NGSS). To achieve the goal of the research, the researcher prepared a measure of creative problem-solving skills, and the proposed program based on science standards for the next generation (NGSS), including: the teacher's guide and the student's activity booklet. The research tools and educational materials were applied to two research groups, consisting of (33) students in the experimental group, and (33) students in the control group of students from Umm Jamil Al-Amriya Primary School for Girls affiliated to the General Administration of Al-Jahra Educational District, in the first semester of the academic year 2022. / 2023 AD. The results of the research showed that there were statistically significant differences between the mean scores of the experimental and control groups in the post-application of the creative problem-solving skills scale in favor of the experimental group, and the presence of statistically significant differences between the mean scores of the experimental group in the pre and post-applications of the creative problem-solving skills scale as a whole in favor of the post-application. The results of the research also showed the effectiveness of the proposed program based on science standards for the next generation (NGSS) in developing creative problem-solving skills for fifth-grade female students. The researcher also recommended the need to pay attention to the development of creative problem-solving skills among primary school students, with some proposals for future research.
Keywords: الاستراتيجيات التعليمية -- الإبداع الفكري -- العمليات العقلية -- طلبة المرحلة الابتدائية -- الكويت